Curiouser and curiouser : Margaret Mahy's novels for adolescents : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy at Massey University - Hensman, Stephen Trevor (Massey University, 1996)
This thesis is a study of the interconnections between Margaret Mahy's novels for adolescents. It argues that whilst interconnected networks infuse the oeuvre with appropriate material for adolescents, some textual elements exceed the limitations of all but the most sophisticated adolescents. After an introductory chapter, Chapter Two proposes a typology of structure in New Zealand novels for adolescents. It finds that Mahy's novels are archetypes of the hope-inducing structures identifiable in New Zealand novels for adolescents generally. It also finds that Mahy adapts structure to the stage of adolescence she is writing for. Chapter Three discusses the generic content and stylistics in the Mahy oeuvre. It argues that even though the content is eminently appropriate for adolescents, some elements of style are not. Chapter Four argues that knowledge of the various networks enriches response, guides interpretation and highlights Mahy's ability to pitch content at an appropriate level for adolescence, but again argues that some subtleties of style are too sophisticated for an adolescent audience. Chapter Five argues that understanding of each novel is expanded by identifying points which imply one reader at the expense of others. Hence, this thesis concludes that meaning and response multiply in Mahy's texts in proportion to (1) knowledge of Mahy's unique interconnecting textual elements and (2) the number of Mahy's implied readers inhering in the actual reader.
Keywords: Mahy, Margaret; Criticism and interpretation